2004
DOI: 10.1212/01.wnl.0000147469.18313.3b
|View full text |Cite
|
Sign up to set email alerts
|

MCI conversion to dementia and the APOE genotype

Abstract: Fluoro-2-deoxy-d-glucose-PET measures may improve prediction of the conversion to Alzheimer disease, especially in combination with the APOE genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
226
4
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(260 citation statements)
references
References 41 publications
26
226
4
4
Order By: Relevance
“…This is in accordance with the majority of previous studies, showing that functional abnormalities in the parietal cortex have the highest predictive values for the future development of AD compared to other brain regions [1,6,8,[18][19][20]25]. However, this is not an unequivocal finding as some other studies have suggested that decreased rCBF in the posterior cingulated gyrus is superior in detecting incipient AD among subjects with MCI [22,23,27].The reason for this discrepancy is unknown, although differences in instrumentation and variations in the affection of brain areas in this heterogeneous population of subjects with MCI may be possible explanations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the majority of previous studies, showing that functional abnormalities in the parietal cortex have the highest predictive values for the future development of AD compared to other brain regions [1,6,8,[18][19][20]25]. However, this is not an unequivocal finding as some other studies have suggested that decreased rCBF in the posterior cingulated gyrus is superior in detecting incipient AD among subjects with MCI [22,23,27].The reason for this discrepancy is unknown, although differences in instrumentation and variations in the affection of brain areas in this heterogeneous population of subjects with MCI may be possible explanations.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, results from flourodeoxyglucose (FDG)-positron emission tomography (PET) studies have shown decreased metabolism in temporo-parietal regions or posterior cingulate cortex in subjects with MCI who will subsequently develop AD [1,8,11,25].…”
Section: Introductionmentioning
confidence: 99%
“…FDG-PET studies of presymptomatic individuals carrying autosomal dominant mutations responsible for early-onset familial AD also show consistent hypometabolism in these regions, as long as 15 years before symptoms onset (7,8). Studies in MCI, considered by many as a transitional state between healthy aging and dementia (13), have shown severe hypometabolism in these same brain regions among MCI patients before converting to AD as compared with those who remained stable over time (9)(10)(11)20). We recently showed that reduced MTL CMRglc in normal elderly is a risk factor for declining to MCI and AD (15,16).…”
Section: Discussionmentioning
confidence: 92%
“…For all analyses, results were considered significant at P Ͻ 0.05 after correction for multiple comparisons according to the SVC (47). We used the MRIcro package (www.psychology.Nottingham.ac.uk/ staff/cr1/mricro.html) to create a masking image from a set of predefined AD-related bilateral regions of interest, including the MTL (hippocampus and parahippocampal gyrus, BA 28/35), PCC/ precuneus (BA 23/31/7), inferior parietal lobule (BA 40/39), superior and middle temporal gyrus (BA 21/22/37), and prefrontal cortex (BA 8/9/10) as candidate areas for CMRglc alterations (11). The mask was then applied to the full volume of data, and results were examined at P Ͻ 0.05 after correction for the number of comparisons in the searched volume defined by the masking image (234,566 mm 3 corresponding to 69,501 voxels, and 55.8 resolution elements) (47).…”
Section: Fdg-petmentioning
confidence: 99%
See 1 more Smart Citation